SOCIAL SIGNIFICANCE OF PHILOSOPHY OF CONSCIOUSNESS AND UNCONSCIOUSNESS - Muratova Dildora Abdumannopovna (Western European Studies, 2024)
In this article, we tried to reveal the levels of human consciousness and unconsciousness under the scientific theory of various psychologists. the sociality of a person leads to the emergence of consciousness or unconsciousness of self-awareness in his spiritual world. A person understands himself, not only other people but also by understanding the framework of material and spiritual activities carried out by them. In the process of selfawareness, a person's ability to separate himself from the world around him and his relationship to it was revealed.
Keywords: Man; consciousness; unconsciousness; literature